Synthesis and photo activity of flower-like anatase TiO2 with {001} facets exposed - Zhao, Y.; Zhao, Q.; Li, Xin Yong; Hou, Y.; Zou, X.; Wang, J.; Jiang, T.; Xie, T. (2012)
Developing photocatalysts with specific morphology promises good opportunities to discover the geometry-dependent properties. Herein, flower-like anatase TiO2 assemblies with dominant {001} facets exposed were successfully synthesized via a simple, economical hydrothermal route with titanium sulfate and hydrofluoric acid. Their surface morphology and structure were investigated by scanning electron microscopy, transmission electron microscopy, selected area electron diffraction, X-ray diffraction, and Brunauer-Emmet-Teller N2 gas adsorption-desorption isotherms. The optical property and the photo-induced charge carriers of the flower-like TiO2 were studied by UV-vis diffuse reflectance spectroscopy and transient photovoltage technique. The flower-like TiO2 particles exhibited a good photocatalytic activity in degrading rhodamine B. © 2011 Elsevier B.V.